2015
DOI: 10.1017/cjn.2015.304
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Motor Aspects of Parkinson’s Disease Associated with Dysphagia

Abstract: Background: Dysphagia is a common symptom and an important prognostic factor in Parkinson's disease (PD). Although cognitive and motor dysfunctions may contribute to dysphagia in patients with PD, any specific association between such problems and swallowing functions is unclear. Here, we examined the potential relationship between cognitive/motor components and swallowing functions in PD. We evaluated the contributions of cognition and motor function to the components of swallowing via video fluoroscopic swal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
3
11
0
3
Order By: Relevance
“…Like previous studies, the present study revealed that dysphagia is significantly correlated with UPDRS and modified Hoehn and Yahr scale [ 30 , 31 ] in contrast to the others [ 32 , 33 ] which showed that the disease stage (UPDRS total and Hoehn and Yahr rating) was not correlated to swallowing difficulties which may be explained by the relatively early stage of PD in our patients (H&Y scale< 3), the shorter duration of illness (4.7 ± 2.2) and the usage of different scores for evaluation of dysphagia.…”
Section: Discussionsupporting
confidence: 87%
“…Like previous studies, the present study revealed that dysphagia is significantly correlated with UPDRS and modified Hoehn and Yahr scale [ 30 , 31 ] in contrast to the others [ 32 , 33 ] which showed that the disease stage (UPDRS total and Hoehn and Yahr rating) was not correlated to swallowing difficulties which may be explained by the relatively early stage of PD in our patients (H&Y scale< 3), the shorter duration of illness (4.7 ± 2.2) and the usage of different scores for evaluation of dysphagia.…”
Section: Discussionsupporting
confidence: 87%
“…In healthy participants, disruptive stimuli might alter feeding, but had little effect on oropharyngeal swallowing [ 29 ]. A study in Parkinson's disease patients suggested that there are significant correlations between frontal/executive or learning/memory functions and the oral phase of swallowing, whereas the pharyngeal phase showed weak correlations with frontal functions [ 30 ]. In Alzheimer's disease (AD), dysphagia has also been thought to be associated with cognitive impairment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic signs of Parkinson's disease—bradykinesia, rigidity, and tremor—have been linked to dopamine loss resulting from neuronal death in the substantia nigra [ 2 , 4 , 5 ]. However, it is becoming clear that damage occurs on a larger scale, throughout the nervous system in PD, and that many symptoms are not responsive to treatments targeting dopamine loss [ 6 ], including problems with eating and swallowing [ 7 , 8 ]. Such problems are frequent in patients with Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%